(untitled) (The Research of Medical Science Review, 2024)
The purpose of this study is to review the literature on competency-based medical education (CBME) principles and to identify some preventative strategies. Integrating competency-based medical education (CBME) into the standard curriculum is a significant difficulty. This study emphasize its practical implementation.